PRIORITIES OF THE STATE POLICY OF ECONOMIC GROWTH IN THE CONDITIONS OF RESOURCE LIMITATIONS - NAKONECHNA, Nataliya; HRADYUK, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Ukraine’s economic growth is characterized by significant instability and excessive dependence on external factors, and the state's economic policy is not based on an appropriate resource-based model of economic development. At the same time, the quality of Ukraine’s resource potential (labor, material and technical, natural, etc.) is deteriorating. All this significantly hinders further economic growth of the country and increases the urgency of substantiating goals and developing conceptual foundations of economic development based on a critical assessment and use of available limited resources. Factors that prevent sustainable economic growth of Ukraine include: constant and systematic politicization of the state’s actions in the field of economic policy, lack of heredity and alternative strategic planning of the state’s economic development; low level of economic security of entrepreneurship and lack of state guarantees of ownership rights; high level of monopolization of socio-economic life in the state; excessive administrative and financial centralization of power and rigid administrative hierarchy; inefficient use of state budget funds; lack of stable «rules of the game»; low culture and distorted nature of socio-economic morality; strengthening of structural deformations in the national economy. The existing inconsistency, non-systematic state economic policy and lack of modeling of economic growth of Ukraine are already a threat to the economic security of the state. State authorities are invited to implement measures aimed at ensuring a mandatory alternative to the strategic planning of the country’s economic development; formation in society of the ideology of «transition» to another quality of economic growth; creation of a system of incentives for social legitimization of shadow income and property, ensuring investments in innovative, scientific and technical development, education and the social sphere; recognition by all socio-political groups of common system-forming principles and priorities of economic growth; ensuring the liberalization of the state's economic policy.
Keywords: government policy; economic growth; resources; limitations; priorities